1981 Reported grain dust explosion incidents grain storage and processing handling facilities, United States - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were twenty-one dust explosions reported in the U.S. in 1980 according to Robert W. Schoeff, Kansas State University. This compares to 44 in 1980.
Keywords: Grain dust; Dust explosions